Integrated thermoelectric sensors based on quantum dot superlattice for thermal management applications. (4th August 2020) - Savelli, Guillaume; Colonna, Jean-Philippe; Keller, Matthias; Coudrain, Perceval; Wendler, Daniel; Goeppert, Jacob; Manoli, Yiannos; Faucherand, Pascal; Royer, Agnès
Abstract: We have developed high sensitivity integrated micro-thermoelectric sensors (µTESs), based on complementary metal-oxide-semiconductor (CMOS) technology. These sensors have been developed from SiGe and quantum dot superlattice (QDSL) materials. QDSLs consist of TiSi2 nanoparticles embedded into a SiGe matrix. This is the first time that thermoelectric devices integrate such silicon-based nanostructured materials. We have shown that all QDSL-based thermoelectric sensors present higher performances than SiGe-based ones. QDSL-based µTESs show high voltage factors equal to 6.92 V K −1 cm −2, higher than other CMOS compatible thermal sensors from literature. Their compactness and fast response time (<4 ms) make them very good candidates for thermal management applications. We have also developed a dedicated read-out interface to manage signals from several µTESs at the same time, offering a global solution for thermal mapping of CMOS circuits.